Analysis of the Application of the Principles of Good Corporate Governance on Company Performance at the Sutan Raja Amurang Hotel - Meggy Kuswara Toalu; Stanly Alexander; Natalia Gerungai (Formosa Journal of Applied Sciences, 2023)
The hotel business is a business in the service sector so that in practice it requires human resources in operational activities, of course with this business it can help create jobs that can reduce unemployment in this country. So, in its management, the management is expected to be able to apply the principles of Good Corporate Governance to maintain business development so that it can have a positive impact. From this statement, this research was made to find out whether the procedures for implementing GCG had been carried out properly by the Sutan Raja Amurang Hotel. This study uses a qualitative method with a descriptive approach, where data is collected through interviews with management, and looks at the conditions directly so that they can describe the actual situation. The research results show that the implementation based on GCG principles has been implemented properly.